Effects of Apparent Temperature on the Incidence of Ventricular Tachyarrhythmias in Patients With an Implantable Cardioverter–Defibrillator: Differential Association Between Patients With and Without Electrical Storm - Huang, Hui-Chun; Suen, Pei-Chin; Liu, Jih-Shin; Chen, Cheryl Chia-Hui; Liu, Yen-Bin; Chen, Chu-Chih (Frontiers in Medicine, 2021)
Background: Electrical storm (ES) has profound psychological effects and is associated with a higher mortality in patients with implantable cardioverter–defibrillator (ICD). Assessing the incidence and features of ES, is vital. Previous studies have shown winter peaks for ventricular tachyarrhythmia (VTA) in ICD patients. However, the effects of heat with a high relative humidity remain unclear. Thus, this study aimed to assess the nonlinear and lagged effects of apparent temperature (or heat index [HI]) on VTA among patients with and without ES after ICD implantation. Methods: Of 626 consecutive patients who had ICDs implanted from January 2004 to June 2017 at our hospital, 172 who experienced sustained VTAs in ICD recording were analyzed, and their clinical records were abstracted to assess the association between VTA incidence and HI by time-stratified case-crossover analysis. Cubic splines were used for the nonlinear effect of HI, with adjustment for air pollutant concentrations. Results: A significant seasonal effect for ES patients was noted. Apparent temperature, but not ambient temperature, was associated with VTA occurrences. The low and high HI thresholds for VTA incidence were <15℃ and >30℃, respectively, with a percentage change in odds ratios of 1.06 and 0.37, respectively, per 1℃. Lagged effects could only be demonstrated in ES patients, which lasted longer for low HI (in the next 4 days) than high HI (in the next 1 day). Conclusion: VTA occurrence in ICD patients was strongly associated with low HI and moderately associated with high HI. Lagged effects of HI on VTA were noted in patients with ES. Furthermore, patients with ES were more vulnerable to heat stress than those without ES. Patients with ICD implantation, particularly in those with ES, should avoid exposure to low and high HI to reduce the risk of VTAs, improve quality of life and possibly reduce mortality.